THE CONSTRUCTION OF INDIGENOUS IDENTITY BASED ON PESANTREN; ANALYSIS OF FAMILY LEADERSHIP FACTORS IN SHAPING SELF-IMAGE OF CHILDREN - Nu'man, Agus (PEDAGOGIK : JURNAL PENDIDIKAN, 2023)
The son of a kyai, who is expected to become the successor in the struggle of leadership and management of the pesantren, has been prepared with a caregiving pattern that is distinctly different from other families. The deeply rooted values of the pesantren tradition and the kyai's family are transmitted through the kyai's distinctive caregiving pattern. Therefore, the purpose of this research is to understand the formation of a unique self-image through the kyai's leadership. This study employs a qualitative approach and a case study methodology. Data analysis in this research uses the Miles and Huberman data analysis technique, which includes data reduction, data display, and verification. Based on the findings of this research, the formation of a pesantren-based self-image identity through the kyai's leadership is achieved through the exemplary role of the family, habituation, indoctrination, and spiritual understanding.